2009
DOI: 10.1093/abbs/gmn009
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and protective immunity in mice of a gene encoding the diagnostic antigen P-29 of <italic>Echinococcus granulosus</italic>

Abstract: Taeniid tapeworm Echinococcus granulosus is the causative agent of Echinococcosis, an important zoonosis with worldwide distribution. In this study, a diagnostic antigen P-29 was cloned from E. granulosus and expressed in Escherichia coli. Sequence analysis showed that EgP-29 contains 717-bp open reading frame and encodes a protein of 238 amino acid residues with a predicted molecular weight of 27.1 kDa. The recombinant EgP-29 (rEgP-29) could be recognized with antimice sera in Western blotting. The specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…1 O.D. value profiles of IgGs and IgE in immunized mice before and after infection Different stages were selected for antibodies examination: 0 week(before immunization), 2nd(2 weeks after first immunization), 4th(2 weeks after 2nd immunization), 6th(2 weeks after 3 rd immunization), 7th(1 week after infection), 10th(4 weeks after infection) and 31st(25 weeks after infection) way, the present approach referenced and improved not only previous studies that investigated the immune response generated by inoculation of mice with live or dead PSC (Zhang et al 2003;Hernandez-Pomi et al 1997;Severi et al 1997;Dematteis et al 1999;Al-Qaoud and Abdel-Hafez 2005) but also the immunoprotection studies of recombinant protein in recent years (Li and Wang 2007;Shi et al 2009;Lin and Ding 2004). Evidently, immunization with rEg.myophilin leads to effective immunity protection compared with the other two control groups, between which there is no significant difference in cyst load reduction.…”
Section: Discussionmentioning
confidence: 73%
“…1 O.D. value profiles of IgGs and IgE in immunized mice before and after infection Different stages were selected for antibodies examination: 0 week(before immunization), 2nd(2 weeks after first immunization), 4th(2 weeks after 2nd immunization), 6th(2 weeks after 3 rd immunization), 7th(1 week after infection), 10th(4 weeks after infection) and 31st(25 weeks after infection) way, the present approach referenced and improved not only previous studies that investigated the immune response generated by inoculation of mice with live or dead PSC (Zhang et al 2003;Hernandez-Pomi et al 1997;Severi et al 1997;Dematteis et al 1999;Al-Qaoud and Abdel-Hafez 2005) but also the immunoprotection studies of recombinant protein in recent years (Li and Wang 2007;Shi et al 2009;Lin and Ding 2004). Evidently, immunization with rEg.myophilin leads to effective immunity protection compared with the other two control groups, between which there is no significant difference in cyst load reduction.…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, other studies have reported variable levels of protection with purified antigens. The protection rates of a recombinant vaccine (EG95) ranged from 86% to 99.3% in studies conducted by Lightowlers et al (1999) and Heath et al (2003), respectively, and Shi et al (2009) reported complete immunity persisting for more than a year after vaccination. In another study conducted by Li et al (2012), mice vaccinated with rEg14-3-3 and challenged with protoscolices were provided with significant protective immunity at a rate of 84.47%.…”
Section: Discussionmentioning
confidence: 99%
“…granulosus P29 (rEgP29) vaccination provides effective protection of mice against challenge infection with E . granulosus protoscoleces [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination of mice with bacterially produced recombinant EgP29 (rEgP29) was shown to lead to significant protective immunity, resulting in 96.6% protection against challenge infection with E . granulosus protoscoleces [ 56 ]. In this study, we examined the antigenicity and immunogenicity of recombinant E .…”
Section: Introductionmentioning
confidence: 99%